Salicylic acid mitigates Pb stress in nicotiana tabacum - Abdul Halim, Nurul Izzah; Phang, Ing Chia (Razi Publishing, 2017)
The exposure of plants to Pb stress increases the generation of reactive oxygen species (ROS) including O2–, H2O2 and ˉOH. ROS are highly reactive substances that capable of altering normal cellular metabolism via oxidative damage to membranes, proteins, and nucleic acids. Compound involves in the detoxification of Pb stress is important to reduce the toxic effect of Pb. Stress signaling compounds like salicylic acid (SA) is one of the plant defense mechanisms to mitigate Pb toxicity. This study aimed to observe the effect of SA on the morpho-physiology, accumulation of Pb content and the production of O2– and H2O2 of N. tabacum grown under Pb stress. N. tabacum was propagated and treated with SA and Pb treatments. Then, the morpho-physiology of N. tabacum was observed and measured, histochemical staining of diaminobenzidine (DAB) and nitro blue tetrazolium (NBT), and Inductively coupled plasma mass spectrometry (ICP-MS) were conducted to assesses the effect of SA on the accumulation of O2– and H2O2, and Pb content in Pb-treated N. tabacum. The finding of this study showed the application of SA improved growth parameters, diminished the accumulation of oxidative stress as well as reduced Pb content. SA might detoxify Pb, thus alleviate Pb toxicity.